Potensi dan Tantangan Pariwisata Maritim Kepulauan Seribu - Ahmad Firza Fauzan; Agussalim Burhanuddin (Student Scientific Creativity Journal, 2023)
Maritime tourism in the Thousand Islands has become a significant component in the advancement of Indonesian tourism. The Thousand Islands offer great potential as a maritime tourist destination due to its coral reef ecosystems, marine biodiversity, and beautiful beaches. However, the development of maritime tourism in this region faces various challenges, including coral damage, marine pollution, and issues related to island accessibility. Other challenges encompass security, transportation, and regulations pertaining to tourism development. This study employs a qualitative approach and literature review techniques to delineate the potential and challenges of maritime tourism. The research findings highlight development strategies, including environmental preservation, improved accessibility, and collaboration among the government, stakeholders, and local communities. This research provides insights into the potential and challenges of maritime tourism in the Thousand Islands, serving as a guide for decision-makers in fostering sustainable tourism development in the region. With this profound understanding, it is hoped that development strategies can sustain the allure of tourism in the Thousand Islands while preserving the environment and enhancing the well-being of local communities.